Hourglass Contractions Complicating Bipartite Placental Delivery (AYUSHDHARA, 2024)
Bipartite retained placenta, a rare complication where the placenta remains partially attached due to abnormal separation, can pose significant risks to maternal health. Hourglass contraction, characterized by a specific uterine contraction pattern, has been suggested as a potential underlying cause. Objective: This case study aims to highlight the role of hourglass contraction in the occurrence of bipartite retained placenta, examining its presentation, management, and outcomes. Methods: A detailed case study of a patient who experienced bipartite retained placenta after a vaginal delivery at term. The patient’s clinical history, labor details, and intraoperative findings were reviewed. Hourglass contraction was observed during labor, resulting in a partial separation of the placenta. Results: She had bipartite placenta which has been removed digitally under general anaesthesia. The mother and baby recovered by appropriate treatment and care with no long-term complications reported. Conclusion: This case study underscores hourglass contraction as a contributory factor in bipartite retained placenta. Recognizing this contraction pattern can enhance diagnostic accuracy and inform targeted management strategies. Future studies are recommended to explore the frequency of hourglass contractions in retained placenta cases and develop preventive measures.